The construction and validation of an achievement test in first year high school English grammar - Dela Cruz, Frolin Morales 1937- (s.n.], 1969)
This study is an exploratory attempt to construct and validate an achievement test in the first year high school English grammar. It aims to illustrate the processes involved in test development and to show what teachers can do by way of construction.